1994
DOI: 10.1177/095632029400500503
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a Sulfated Polysaccharide Extracted from the Red Seaweed Aghardhiella Tenera against Human Immunodeficiency Virus and Other Enveloped Viruses

Abstract: A galactan sulfate (GS) was isolated from an aqueous extract of the red seaweed Aghardhiella tenera and partially purified. GS inhibited the cytopathic effect of human immunodeficiency virus type 1 (HIV-1) and type 2 (HIV-2) in MT-4 cells at concentrations 10-fold higher than those required for the inhibition by dextran sulfate (MW 5000) of the cytopathic effect of HIV-1 and HIV-2 (50% inhibitory concentrations: 0.5 and 0.05119 mr", respectively). GS suppressed syncytium formation between MOLT-4 cells and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 36 publications
(30 reference statements)
0
60
0
1
Order By: Relevance
“…Here we demonstrated the antiviral activities of two sulphur-containing anionic exopolysaccharides from cyanobacterium A. platensis (TK V3) and from rhodophyt P. purpureum (EPS) against the OPV VACV and ECTV.So far, there have been few reports of anti-OPV polyanionic activities derived from phototrophic microorganisms [8,35]. Production of the compounds in monoseptic cultures of microalgae and cyanobacteria occurred in photo-bioreactors and can be scaled up successfully [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we demonstrated the antiviral activities of two sulphur-containing anionic exopolysaccharides from cyanobacterium A. platensis (TK V3) and from rhodophyt P. purpureum (EPS) against the OPV VACV and ECTV.So far, there have been few reports of anti-OPV polyanionic activities derived from phototrophic microorganisms [8,35]. Production of the compounds in monoseptic cultures of microalgae and cyanobacteria occurred in photo-bioreactors and can be scaled up successfully [36].…”
Section: Discussionmentioning
confidence: 99%
“…and the type of anion (sulfate, sulphone, carboxylate, phosphate) -are mainly the molecule size, its conformation, charge frequency or charge spreading [9]. It is generally assumed that polyanionic compounds interact with positively charged viral membrane glycoproteins of enveloped viruses and thereby inhibit initial viral attachment to negatively charged heparan sulfate proteoglycans on the cellular membrane [8]. Referring to VACV, the interaction between A27L membrane gene product and heparan sulfate was revealed by Chung et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action may be attributed to inhibition of the interaction between the viral glycoprotein gp120 and the cellular CD4 receptor. In general, polyanionic compounds exhibit their anti-HIV activity by binding to the V3 domain of gp120 (Baba et al, 1988b;Nakashima et al, 1989;Schols et al, 1991, 1992, Witvrouw et al, 1994. Although the polyanions inhibit the binding of herpesviruses and HIV, and thus indirectly prevent the subsequent fusion process as well, their effects on the replication of influenza virus can be ascribed primarily to inhibition of virus-cell fusion (Lüscher-Mattli & Glück, 1990;Ikeda et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…(1990bSchols et el. ( , 1992, Witvrouw et al (1991Witvrouw et al ( , 1992Witvrouw et al ( , 1994 and Damonte et al (1994). :"…”
Section: Inhibition Of Syncytium Formationunclassified
“…Shortly after the identification and isolation of the virus responsible for the acquired immune deficiency syndrome (AIDS) (subsequently named the human immunodeficiency virus, HIV), several groups, following a suggestion of De Clercq (1986), demonstrated that heparin and other polysulfates are potent and selective inhibitors of HIV-1 replication in cell culture (Ito et el., 1987(Ito et el., , 1991suya et el., 1988;Mizumoto et ei., 1988;Yoshida et al, 1988;Hirabayashi et el., 1989;Jurkiewicz et el., 1989;Sugawara et al, 1989;Tochikura et al, 1989;Anand et el., 1990a,b;Kaneko et al, 1990;Montefiori et al, 1990;Weiler et al, 1990;Schols et sl., 1990aSchols et sl., , 1991Von Briesen et al, 1990;Aoki et al, 1991;Bagasra et al, 1988Bagasra et al, , 1991Sosa et al, 1991;Handa et al, 1991;Hatanaka et al, 1991;McClure et al, 1991;Moriya et al, 1991Moriya et al, , 1993Otake et al, 1991Otake et al, , 1994Witvrouw et al, 1991Witvrouw et al, , 1992Witvrouw et al, , 1994Mizuno et al, 1992;Uryu et al, 1992;Barzu et al, 1993;Beutler et al, 1993;Damonte et el., 1994). Several polysulfates were also found to be active against a wide variety of enveloped viruses (Baba et el., 1988c;De Clercq, 1990, 1993;Andrei et el., 1991;Schols et al...…”
Section: Introductionmentioning
confidence: 99%